Journey of a committed paleodemographer Farewell to Jean-Pierre Bocquet-Appel - Degioanni, Anna; Herrscher, Estelle; Naji, Stephan (Préhistoires de la Méditerranée, 2021)
This book is dedicated to Jean-Pierre Bocquet-Appel, anthropologist and biologist, one of the founding fathers of palaeodemography in France, who died in 2018. Known and recognised worldwide, he contributed to the development of new techniques for estimating the age at death of skeletal assemblages and promoted the introduction of estimators in palaeodemography. He also participated in the emergence of spatial demography and multi- agent modelling, particularly of Neolithic farmers. We owe him a considerable advance in the understanding of demographic processes linked to the great transitions that humans have experienced in different parts of the world with the discovery of the signature of the demographic transition implied in the passage of societies from a collection economy to an agricultural economy. This book offers a journey to the heart of his life as a researcher, taking in turn, in a diachronic and multidisciplinary approach, anthropological demography from prehistory to the contemporary period. It also paints a generous portrait of this committed man who has never ceased to work for his discipline, whether through a reflective approach to the history of science and epistemology or the transmission of his knowledge to younger generations. This book invites you to an original and innovative experience on the borders of a rare discipline, paleodemography.